Agent Technology Approach To Improve KUIM Leave Management System - Yuseni, Ab Wahab (2010)
Malacca Islamic College University is a centre of higher learning institution owned by the Malacca state government which has about 150 employees. The staff used the leave system to take annual leave. However, there are some problems faced by the leave system. There is no specific process for Head Of Department to approve the staff‟s leave when no reference to the event in KUIM, public holidays and tasks for each employee in KUIM. It is difficult for Head Of Department to confirm the leave if the program does not know which event will take place in KUIM. Moreover, there is also Head Of Department who did not know the tasks of their employee before approving the leave. Therefore, the objectives of this study are to create a device that can help the head of department to control and monitor the event to be held in KUIM program throughout the year, holidays and tasks for each employee in KUIM. The proposed method to develop the new leave system is agent technology. This agent is a method that helps to overcome the problem faced by the existing KUIM leave system. Benefit from the new leave system is the head of department able to monitor the program and tasks in KUIM before approving their application. When it‟s done, the LMS leave system will get two system tool which is KUIM event and KUIM employee task. There is also a tool for public holiday for the staff to refer when applying leave. Ultimately, this agent tool can overcome the problem faced by the existing KUIM leave system. However, this system requires further enhancement to facilitate the head of department to approve the staff application.